LNG vapor barrier and obstacle evaluation: wind-tunnel simulation of 1987 Falcon spill series: data report - Shin, Seong-Hee, author; Meroney, Robert N., author; Neff, D. E., author; Fluid Mechanics and Wind Engineering Program, Department of Civil Engineering, Colorado State University, publisher (Colorado State University. Libraries, 1989)
Measurements of the behavior of simulated liquefied natural gas clouds dispersing over small-scale model placed in meteorological wind tunnels permits evaluations of the fluid physics of dense cloud movement and dispersion in a controlled environments. A large data base on the interaction of simulated LNG plumes with the Falcon test configuration of vapor barrier fences and vortex generators was obtained. The purpose of the reported test program is to provide post-field-spill wind-tunnel experiments to augment the LNG Vapor Fence Field Program data obtained during the Falcon Test Series in 1987. The goal of the program is to determine the probable response of a dense LNG Vapor cloud to vortex inducer obstacles and fences, examine the sensitivity of results: to various scaling arguments which might augment limit, or extend the value of the field and wind-tunnel tests, and identify important details of the spill behavior which were not predicted during the pretest planning phase.
CER89-90SHS-RNM-DEN-11.
GRI project manager Ted Williams.
August, 1989.
Keywords: Liquefied natural gas